A comparison of scale attributes between interval-valued and semantic differential scales - Themistocleous, Christos; Pagiaslis, Anastasios; Smith, Andrew; Wagner, Christian (My University, 2019)
This article presents the results of an exploratory study comparing interval-valued scales (IVSs) and semantic differential scales (SDSs). The article investigates consumer perceptions regarding specific scale attributes and utilizes a controlled, between-subjects, experimental pen-and-paper design to assess the preferences of respondents when using the IVSs and SDSs. The rationale of this comparison lies with the fact that the newly introduced IVS has a built-in mechanism that allows the direct capture of respondent uncertainty toward the asked question, a feature that is absent from the SDS and other widely used, single-point capturing scales in marketing research such as the Likert and Stapel. Results show that overall consumer preferences of the IVS and SDS are equal, although “speed of use” results favor the IVS. The consistency of respondent evaluations regarding the two scales may indicate their interchangeability in marketing research and opens up pathways for future exploration of IVSs for the accumulation of more reliable and robust results. The main contribution of the article is the introduction of a novel IVS, within the context of marketing, for collecting respondent answers while also directly capturing respondent uncertainty. Furthermore, this article adds to the discussion of consumer perceptions and preferences regarding different scales, scale development, and optimal rating scales that may lessen ambiguity for survey respondents and researchers.
Keywords: Experiments; Interval-valued scale; Scale attributes; Semantic differential scale; Survey